Evaluation of the operation scheduling application (SIJO) in an effort to reduce the number of cancellation of operations at Dr. Mohammad Hoesin Hospital Palembang - Masdahlena; Aulia Widyastuti (RSUP Dr Moh Hoesin Palembang, 2024)
The high rate of surgical cancellation has an impact on the low hospital performance assessment. Based on the results of the first semester achievement of 8.75% with a score of 0.5, it shows that it is far from the target achievement < 1%. This study aims to evaluate the application of the SIJO application in an effort to reduce the cancellation rate at Dr. Mohammad Hoesin Palembang Hospital using mixed methods with a quantitative research design using cross-sectional and qualitative research design using Miles and Huberman. The results of quantitative research showed that there was a significant relationship between the number of cancelled operations with laboratory results (COVID-19) (p-value 0.0001); did not get anesthesiologist approval (p-value 0.0001); ICU room availability (p-value 0.017); and blood availability (p-value 0.0001), and there was an insignificant relationship between the number of cancelled operations and the unavailability of pharmaceutical equipment (p-value 0.227). From the results of qualitative analysis conducted by in-depth interviews with research respondents, it is known that the Operation Scheduling Application (SIJO) is useful in the regularity of scheduling operations, effective in reducing the number of canceled operations. The most common obstacles encountered in using the SIJO application are swab results that sometimes do not appear automatically which have an impact on the operation scheduling process, the passwords of all users are the same so that misuse of SIJO accounts can occur and the slow RSMH internet network.